Deployment of nets - Mumbai Archive Project Team (Jio Institute, 2024)
In the open sea, Kolis deploy surrounding nets (used to encircle a school of fish near the water surface) and drift nets (usually set at or near the water surface and held in place by floats along the top edge and weights along the bottom edge).